Parallelism in parasite infections in two populations of polymorphic Arctic charr (Salvelinus alpinus L.) in northern Norway - Refsnes, Birgitte (UiT Norges arktiske universitet, 2014)
The composition and structure of a component community can vary widely across host populations of the same host species. Revealing the causes and consequences of geographical variation in parasite community composition is of great importance in order to determine parasites role in an ecosystem. Divergence in parasite infections among sympatric polymorphic Arctic charr is commonly associated with divergence in food and habitat preferences, and offers a great opportunity to test the factors determining parasite community composition. By contrasting the sympatric living morphs in Fjellfrøsvatn, and in Skogsfjordvatn, I aimed at assessing if the observed differences in feeding and habitat characteristics among the morphs, both within and across lakes, are reflected in their parasite community composition. The study revealed large intra-lake differences in parasite community between the sympatric morphs within and across lakes. The LO-morphs found in the littoral-pelagic habitat had higher parasite diversity than the PB-morphs occupying the profundal habitat. Morphs in the littoral-pelagic zone had also higher intensities of parasites transmitted through copepods and littoral amphipods, whereas morphs in the profundal had higher intensity of parasites transmitted through benthic amphipods. The highest parasite diversity was found in the piscivorous PP-morph residing in the profundal zone in Skogsfjordvatn. This morph also had highest parasite loadings, apparently accumulating parasites by predating upon the PB-morph, juvenile individuals from the LO-morph and sticklebacks. The study also revealed a parallelism in parasite species composition between the LO-and PB-morphs that occurred in both lakes. These similarities reflect the similar diet and habitat characteristics of the morphs, as well as the exposure to similar abiotic conditions in their respective habitats.